Flexible and stable quasi-solid-state zinc ion battery with conductive guar gum electrolyte. (December 2019) - Huang, Yuan; Zhang, Jiyan; Liu, Jiuwei; Li, Zixuan; Jin, Shunyu; Li, Zigang; Zhang, Shengdong; Zhou, Hang
Abstract: Flexible zinc ion batteries (ZIBs) have been regarded as alternative portable energy storage technology for wearable or flexible electronics due to their low cost and high safety performance. Development of stable solid-state electrolyte with high ionic conductivity is a key to the practical application of ZIBs. Herein, we construct a high rate performance and long cycling life quasi-solid-state ZIB using guar gum bio-polymer electrolyte. The eco-friendly electrolyte synthesized in this work is highly flexible and conductive (1.07 × 10 −2 S cm −1 at room temperature). As a result, our flexible quasi-solid-state ZIBs deliver a high specific capacity (308.2 mAh g −1 at 0.3 A g −1 ), and fast charging and discharging capability (131.6 mAh g −1 at 6.0 A g −1 ). The elastic guar gum electrolyte can effectively suppress the formation of zinc dendrites during cycling, leading to a remarkable cycling cyclability (100% capacity retention after 1900 cycles, 85% capacity retention after 2000 cycles at 6.0 A g −1 ) and high bending durability (81.3% capacity retention after continuously bending to 180° for 1000 cycles). Moreover, the solid-state ZIBs with guar gum electrolyte also function in a wide temperature window (5–45 °C) and deliver a better low-temperature performance than that with aqueous electrolyte. To the best of our knowledge, this is the first work that demonstrates high-performance ZIBs with guar gum as the electrolyte, and achieves the best cycling performance ever reported for ZIBs (Zn–MnO2 ) with solid-state electrolyte. Graphical abstract: Image 1 Highlights: The guar gum electrolyte is highly flexible and conductive. ZIBs using guar gum electrolyte achieve high rate performance and long cycling life. The guar gum electrolyte can suppress the formation of dendrites during cycling. ZIBs with guar gum electrolyte function in a wide temperature window.